Early-life gut mycobiome core species modulate metabolic health in mice - Mackenzie W. Gutierrez; Erik van Tilburg Bernardes; Ellen Ren; Kristen N. Kalbfleisch; Madeline Day; Ewandson Luiz Lameu; Thaís Glatthardt; Emily M. Mercer; Sunita Sharma; Hong Zhang; Ali Al-Azawy; Faye Chleilat; et al. (Nature Communications)
Abstract The gut microbiome causally contributes to obesity; however, the role of fungi remains understudied. We previously identified three core species of the infant gut mycobiome (Rhodotorula mucilaginosa, Malassezia restricta and Candida albicans) that correlated with body mass index, however their causal contributions to obesity development are unknown. Here we show the effects of early-life colonization by these fungal species on metabolic health in gnotobiotic mice fed standard (SD) or high-fat-high-sucrose (HFHS) diets. Each species resulted in bacterial microbiome compositional and functional differences. R. mucilaginosa and M. restricta increased adiposity in mice fed SD, while only R. mucilaginosa exacerbated metabolic disease. In contrast, C. albicans resulted in leanness and resistance to diet-induced obesity. Intestinal nutrient transporter expression was unaffected by the presence of fungi in jejunal enteroids, yet the immune landscape in white adipose tissue was distinctly impacted by each fungal species, suggesting that these phenotypes may be a result of fungal immune regulation. This work revealed that three common fungal colonizers have distinct causal influences on obesity and metabolic inflammation and justifies the consideration of fungi in microbiome research on host metabolism.